Pengaruh Penggunaan Buku Siswa IPA Terintegrasi Nilai Religius Berbasis STEM PjBL Terhadap Sikap Spiritual dan Literasi Sains Siswa - Muhammad Sholehuddin; Ariswan; Insih Wilujeng (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of science student books on the material of Light and Optical Instruments integrated with religious values with the STEM PjBL model approach in improving students' spiritual attitudes and scientific literacy. The study used a quasi-experimental quantitative research method with one group pretest-posttest design. Data collection methods using multiple choice tests and questionnaires. The subjects in this study were 31 students of class VIII C MTs Wahid Hasyim Balung Jember. The results showed that the average N-Gain value of spiritual attitudes was 0.46 with the